2020
DOI: 10.1093/ehjci/jeaa101
|View full text |Cite
|
Sign up to set email alerts
|

The myocardial phenotype of Fabry disease pre-hypertrophy and pre-detectable storage

Abstract: Aims Cardiac involvement in Fabry disease (FD) occurs prior to left ventricular hypertrophy (LVH) and is characterized by low myocardial native T1 with sphingolipid storage reflected by cardiovascular magnetic resonance (CMR) and electrocardiogram (ECG) changes. We hypothesize that a pre-storage myocardial phenotype might occur even earlier, prior to T1 lowering. Methods and results FD patients and age-, sex-, and heart rate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
2
32
0
2
Order By: Relevance
“…GLS identifies subclinical cardiac involvement in a variety of conditions [31]; and in FD, GLS can be impaired even with normal LV wall thickness [15]. Augosto et al have recently described several phases of FD including a silent 'accumulation stage' where LV wall thickness is normal, with evidence of detectable infiltration on CMR with corresponding impairment in GLS on TTE [32]. A previous study that used a binary definition to classify patients into 2 groups-normal versus abnormal ECG (defined as any of the following: prolonged or shortened PQ interval; prolonged QRS duration; the presence of LVH criteria; or t wave inversion), also demonstrated correlation with impaired GLS [33].…”
Section: Correlating Electrocardiographic and Echocardiographic Param...mentioning
confidence: 99%
“…GLS identifies subclinical cardiac involvement in a variety of conditions [31]; and in FD, GLS can be impaired even with normal LV wall thickness [15]. Augosto et al have recently described several phases of FD including a silent 'accumulation stage' where LV wall thickness is normal, with evidence of detectable infiltration on CMR with corresponding impairment in GLS on TTE [32]. A previous study that used a binary definition to classify patients into 2 groups-normal versus abnormal ECG (defined as any of the following: prolonged or shortened PQ interval; prolonged QRS duration; the presence of LVH criteria; or t wave inversion), also demonstrated correlation with impaired GLS [33].…”
Section: Correlating Electrocardiographic and Echocardiographic Param...mentioning
confidence: 99%
“…Mathur et al demonstrated that base-to-apex CS gradient discriminates between AFD patients without hypertrophy or LGE and healthy controls independent of native T1, suggesting that loss of base-to-apex CS gradient may be an early marker of cardiac involvement in AFD [ 85 ]. More recently, Augusto et al described a slightly reduced GLS as a primary cardiac phenomenon, because of the altered myocardial coupling to the systemic vasculature due to systemic endothelial and smooth muscle changes [ 87 ]. However, additional studies will be necessary to validate the utility of CMR speckle tracking in AFD patients.…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Of note, early stages are characterized by endocardial shortening and a lesser degree of QT-dispersion, in contrast to later stages with manifest signs of a cardiomyopathy [7]. Further, in a recently published analysis of ECG parameters in prehypertrophic FD as compared to a normal cohort revealed measures similarly suggestive of these mechanisms [22]. However, since in contrast to the present study, manually analyzed advanced ECG parameters were included, it remains speculative whether an automated ECG analysis with the present statistical approach would have identified the same or other parameters to be significant.…”
Section: Electrocardiographic/electro-anatomical Considerationsmentioning
confidence: 97%